On the Boak Tagalog of the Island of Marinduque - Lopez, Cecilio (The Archive; Vol 1 No 2 (1970): Vol. 1 (New Series), No. 2 (1970), 2024)
Excerpt Generally speaking, we Tagalog inhabitants of the central part of Luzon do not recognize any special Tagalog ‘dialect’. Similar to other people all over the world, we distinguish our richly developed literary language, as to be found in such classical works as ‘Florante at Laura’ by F. Balagtas, ‘Wilhelm Tell ni Schiller’ by Rizal, ‘Pagsusulatan nañg dalawang binibini’ by P. Modesto Castro, from the plainer forms of our colloquial speech. Even when born or residing in Manila, we look upon the Tagalog used in the Province of Bulakan, north of Manila, as upon the best spoken Tagalog, while we easily recognize certain individuals by their intonation — ‘punto’ or ‘puntillo’, as we call it — as belonging to this or that other specific region or locality. Yet we may go pretty far afield in almost all directions where our language is at home, without encountering any real difficulty in conversing with our peasants, mountaineers, or coast dwellers. With all this, there are found in the Tagalog provinces certain peculiarities of expression which, while not constituting a special dialect, contrast with what has just been indicated as ‘Standard Tagalog’, and are worth being investigated by the linguist.